2014
DOI: 10.1016/j.redox.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Mild exposure of RIN-5F β-cells to human islet amyloid polypeptide aggregates upregulates antioxidant enzymes via NADPH oxidase-RAGE: An hormetic stimulus

Abstract: The presence of amyloid aggregates of human islet amyloid polypeptide (hIAPP), a hallmark of type 2 diabetes, contributes to pancreatic β-cell impairment, where oxidative stress plays a key role. A contribution of NADPH oxidase to reactive oxygen species (ROS) generation after cell exposure to micromolar concentrations of hIAPP aggregates has been suggested. However, little is known about β-cells exposure to lower amounts of hIAPP aggregates, similar to those found in human pancreas. Thus, we aimed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…hIAPP is a peptide hormone co-secreted with insulin by pancreatic β-cells, and fibrillar deposits of hIAPP amyloid aggregates in islets of Langerhans are a well known of T2DM. hIAPP aggregation together with oxidative stress (via NADPH-oxidase) leads to hIAPP toxicity, and plays a pivotal role in T2DM pathogenesis [127,128]. Rigacci et al [74] showed that OleA occurrence, during the aggregation process, drove the formation of structurally different aggregates by hindering their binding with the membrane cells, resulting in a decrease of membrane damage, and protection of rat insulinoma cells against aggregate cytotoxicity, the main aspect responsible for cell sufferance.…”
Section: Oleuropein As Anti-amyloid Toolmentioning
confidence: 99%
“…hIAPP is a peptide hormone co-secreted with insulin by pancreatic β-cells, and fibrillar deposits of hIAPP amyloid aggregates in islets of Langerhans are a well known of T2DM. hIAPP aggregation together with oxidative stress (via NADPH-oxidase) leads to hIAPP toxicity, and plays a pivotal role in T2DM pathogenesis [127,128]. Rigacci et al [74] showed that OleA occurrence, during the aggregation process, drove the formation of structurally different aggregates by hindering their binding with the membrane cells, resulting in a decrease of membrane damage, and protection of rat insulinoma cells against aggregate cytotoxicity, the main aspect responsible for cell sufferance.…”
Section: Oleuropein As Anti-amyloid Toolmentioning
confidence: 99%
“…The RAGE receptors will increase oxidative stress by activating the NADPH oxidase (NOX) that induces ROS formation (Fig. 6) [200,201].…”
Section: Vitamin D and Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Thus, the role of JNK is complex in the mediation of distinct cellular response depending on cell contents. In addition, different concentrations of hIAPP could result in different cellular responses, for example, the activation of NADPH-oxidase induced by hIAPP at 60 nM was converse to the concentration at 500 nM [53]. And recent researches were focused on the molecular or signal changes induced by hIAPP at μM levels [1,6,7,16,40,54].…”
Section: Disscussionmentioning
confidence: 99%